ПРОФОРІЄНТАЦІЙНА РОБОТА ЯК НЕВІД'ЄМНА СКЛАДОВА НАВЧАЛЬНО-ВИХОВНОЇ ДІЯЛЬНОСТІ УЧНІВ ОСНОВНОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2008)
In the article certainly essence, maintenance and task of professional orientation work, with students at basic school and methodical recommendations are offered in relation to the improvement of professional information work on the lessons o f labour studies.